Physical activity and sedentary behavior in relation to esophageal and gastric cancers in the NIH-AARP cohort. - Michael B Cook (Public Library of Science (PLoS), 2013)
Introduction Body mass index is known to be positively associated with an increased risk of adenocarcinomas of the esophagus, yet there is there limited evidence on whether physical activity or sedentary behavior affects risk of histology- and site-specific upper gastrointestinal cancers. We used the NIH-AARP Diet and Health Study to assess these exposures in relation to esophageal adenocarcinoma (EA), esophageal squamous cell carcinoma (ESCC), gastric cardia adenocarcinoma (GCA), and gastric non-cardia adenocarcinoma (GNCA). Methods Self-administered questionnaires were used to elicit physical activity and sedentary behavior exposures at various age periods. Cohort members were followed via linkage to the US Postal Service National Change of Address database, the Social Security Administration Death Master File, and the National Death Index. Cox proportional hazards regression models were used to estimate hazard ratios (HR) and 95 percent confidence intervals (95%CI). Results During 4.8 million person years, there were a total of 215 incident ESCCs, 631 EAs, 453 GCAs, and 501 GNCAs for analysis. Strenuous physical activity in the last 12 months (HR(>5 times/week vs. never)=0.58, 95%CI: 0.39, 0.88) and typical physical activity and sports during ages 15-18 years (p for trend=0.01) were each inversely associated with GNCA risk. Increased sedentary behavior was inversely associated with EA (HR(5-6 hrs/day vs. <1 hr)=0.57, 95%CI: 0.36, 0.92). There was no evidence that BMI was a confounder or effect modifier of any relationship. After adjustment for multiple testing, none of these results were deemed to be statistically significant at p<0.05. Conclusions We find evidence for an inverse association between physical activity and GNCA risk. Associations between body mass index and adenocarcinomas of the esophagus do not appear to be related to physical activity and sedentary behavior.